A Review of Prognostic Tools in Heart Failure. (March 2018) - Treece, Jennifer; Chemchirian, Hrak; Hamilton, Neil; Jbara, Manar; Gangadharan, Venkataramanan; Paul, Timir; Baumrucker, Steven J.
A minority of patients with end-stage disease are referred to palliative medicine for consultation in advanced heart failure. Educating stakeholders, including primary care, cardiology, and critical care of the benefits of hospice and palliative medicine for patients with poor prognosis, may increase appropriately timed referrals and improve quality of life for these patients. This article reviews multiple tools useful in prognostication in the setting of advanced heart failure.